2010
DOI: 10.1016/j.vaccine.2010.06.099
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immune reaction prevents immunopathology after challenge with avian influenza virus: A transcriptomics analysis of adjuvanted vaccines

Abstract: To gain more insight in underlying mechanisms correlating to protection against avian influenza virus (AIV) infection, we investigated correlates of protection after AIV H9N2 infection and studied the contribution of different adjuvants to a protective response at host transcriptional level. One-day-old chickens were immunised with inactivated H9N2 supplemented with w/o, Al(OH)(3), CpG or without adjuvant. Two weeks later, birds were homologously challenged and at 1-4 days post challenge (d.p.c.) trachea and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Despite the inoculation of a normalized infectious dose of viruses belonging to the same subtype (H7) and pathotype (LPAI), the use of animals of the same age, sex and species as well as the identification of a comparable viral load in the target samples, the analyses and comparisons of the transcriptome data highlighted the uniqueness of the response among the four experimental groups. This evidence is in line with the results of previous comparative studies implemented using viruses with different virulence in in vitro and in animal models, which demonstrated that differences in the host response cannot be attributed solely to differences in viral replication but rather more to the properties of the individual influenza A virus [66][67][68][69][70][71]. In our study, we aimed to use viruses that have demonstrated very different characteristics in terms of phenotype evolution but in which no genomic differences crucial to LP-HP transition have been recognized.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the inoculation of a normalized infectious dose of viruses belonging to the same subtype (H7) and pathotype (LPAI), the use of animals of the same age, sex and species as well as the identification of a comparable viral load in the target samples, the analyses and comparisons of the transcriptome data highlighted the uniqueness of the response among the four experimental groups. This evidence is in line with the results of previous comparative studies implemented using viruses with different virulence in in vitro and in animal models, which demonstrated that differences in the host response cannot be attributed solely to differences in viral replication but rather more to the properties of the individual influenza A virus [66][67][68][69][70][71]. In our study, we aimed to use viruses that have demonstrated very different characteristics in terms of phenotype evolution but in which no genomic differences crucial to LP-HP transition have been recognized.…”
Section: Discussionsupporting
confidence: 90%
“…Upon aerosol inoculation, large beads (3.7 mm and up) were deposited mainly in the anterior portion of the RT, whereas smaller particles were distributed more evenly (17)(18)(19) The heaviest deposition was observed at the bifurcations of the primary to secondary bronchi (19). A similar deposition was found after aerosol spray with avian influenza virus (20). In chickens, the phenotype and function of MPhs and DCs are poorly defined because of a lack of defined markers, but progress has been made, and in vitro bone marrow-derived DCs (BMDCs) can be cultured and, like mammalian DCs, were shown to express surface CD11, the activation markers MHC II and CD40, and the C-type lectin DEC205 after LPS maturation (21).…”
mentioning
confidence: 53%
“…We chose aluminum (alum) OH, chitosan, cholera toxin B subunit (CT-B), and Stimune as adjuvant for in an aerosolized vaccine with inactivated H9N2. Alum adjuvants are the most widely used adjuvants for human vaccines (Lambrecht et al, 2009) and it is an effective adjuvant in influenza vaccines in mice (Chang et al, 2010) and chicken (Reemers et al, 2010). However, in human influenza trials results are less consistent, with an aluminum phosphate adjuvanted H9N2 WIV i.m.…”
Section: Introductionmentioning
confidence: 99%